The Influence of Perceived Usefulness, Perceived Convenience and Perceived Efficiency On The Use of E-Filing For Individual Taxpayer at KPP Pratama Bulukumba - Nurul Hinayah; Agusdiwana Suarni; Wahyuni Wahyuni (Universitas Muhammadiyah Makassar, 2022)
Research data obtained from questionnaires (primary). The results of the analysis were carried out with multiple linear regression. These results indicate that the perceived usefulness variable with a significance value of 0,014 < 0,05 and t_count is greater than t_table. that is 2,517 > 1,984. From these results, it can be seen that the perceived usefulness variable has a positive and significant effect on the use of E-Filing, the perceived convenience variable shows a significance value of 0,004 < 0,05 and t_count is greater than t_table. that is 2,979 > 1,984. From these results, it can be seen that the perceived convenience variable has a positive and significant effect on the use of E-Filing and the efficient perception variable shows a significance value of 0,004 < 0,05 and t_count is greater than t_table. ie 2,918 > 1,984. From these results it can be seen that the efficient perception variable has a positive and significant effect on the use of E-Filing.